Dampak Edukasi Menyusui dalam Meningkatkan Efikasi Diri dan Keberhasilan Menyusui: Scoping Review - Aulia, Rizka; Ladjar , Yohana Filiberta Lumu; Ersianti, Yuninda Loviana; Fernandez, Veronica; Adnani, Qorinah Estiningtyas Sakilah (ARTERI : Jurnal Ilmu Kesehatan, 2025)
One of the key factors influencing infant health is successful breastfeeding. A mother's perception of self-efficacy plays a crucial role in breastfeeding success, highlighting the need for appropriate breastfeeding education. The limited number of studies that comprehensively evaluate the impact of breastfeeding education on maternal self-efficacy and breastfeeding success prompted this study. This research aims to assess the effectiveness of breastfeeding education in improving both aspects. A scoping review design was employed, using a descriptive analytical approach. Articles utilized were randomized controlled trials (RCTs). Relevant articles were searched using keywords in 4 online databases with inclusion criteria, resulting in 15 articles as the reference sources for this study. Overall, 15 articles stated that breastfeeding education can have positive impacts on both mothers and infants. Three themes were identified regarding the effectiveness of breastfeeding education: sources of breastfeeding education and support (researchers, midwives/healthcare providers, community), educational media (technology, booklets, peer groups), and the impacts of breastfeeding education (self-efficacy, frequency of breastfeeding problems, breastfeeding success). Education is not only provided offline but can also be delivered online by leveraging technological advancements. The effectiveness of breastfeeding education is not only determined by the content delivered but also by the sources of education and the use of educational media, thus potentially leading to increased maternal self-efficacy and breastfeeding success.